Human P-selectin glycoprotein ligand-1 is a functional receptor for enterovirus 71 - Nishimura, Yorihiro; Shimojima, Masayuki; Tano, Yoshio; Miyamura, Tatsuo; Wakita, Takaji; Shimizu, Hiroyuki (Nature medicine, 2009)
Enterovirus 71 (EV71) causes hand, foot and mouth disease, a mild infectious disease that can, however, occasionally lead to severe neurological impairments. These two studies, by Nishimura et al . and Yamayoshi et al ., independently identify two different receptors for EV71—P-selectin glycoprotein ligand-1 ((PSGL-1) and scavenger receptor class B, member 2 (SCARB2) ( pages 728–729 ) and ( pages 798–801 ). Enterovirus 71 (EV71) is a major causative agent of hand, foot and mouth disease (HFMD), a common febrile disease occurring mainly in young children. Although clinical manifestations of HFMD are usually mild and self limiting, a severe EV71 outbreak can lead to a diverse array of neurological diseases. Identification of the specific cellular receptors is crucial for elucidating the mechanism of early virus-host interactions and the pathogenesis of enteroviruses 1 . Here we identify human P-selectin glycoprotein ligand-1 (PSGL-1; CD162), a sialomucin membrane protein expressed on leukocytes that has a major role in early stages of inflammation 2 , 3 , 4 , as a functional receptor for EV71 using an expression cloning method by panning 5 . The N-terminal region of PSGL-1 binds specifically to EV71. Stable PSGL-1 expression allowed EV71 entry and replication, and development of cytopathic effects in nonsusceptible mouse L929 cells. Five out of eight EV71 strains bound soluble PSGL-1 and used intact PSGL-1 as the primary receptor for infection of Jurkat T cells. Three other EV71 strains did not use PSGL-1, suggesting the presence of strain-specific replication of EV71 in leukocytes. EV71 replicated in nonleukocyte cell lines in a PSGL-1–independent manner, indicating the presence of alternative receptor(s) for EV71. The identification of PSGL-1 as a receptor for EV71 sheds new light on a role for PSGL-1–positive leukocytes in cell tropism and pathogenesis during the course of HFMD and other EV71-mediated diseases.